PENGARUH TINGKAT KESEHATAN BANK BERBASIS RGEC TERHADAP FINANCIAL DISTRESS (Studi pada Perusahaan perbankan yang terdaftar di BEI tahun 2015-2017) - Habbi Irsyada Haq; Puji Harto (Diponegoro Journal of Accounting, 2019)
Financial distress is something that often occurs in banking companies due to financial difficulties experienced by banks before facing failure or bankruptcy. In order for banking companies to overcome financial distress conditions, it is necessary to assess the bank's soundness level, namely by RGEC.This study aims to examine the effect of bank soundness with the RGEC method which is proxied by the ratio of Non Performing Loans, Loan to Deposit Ratio, board commissioner activity, audit committee size, Return on Assets, Capital Adequacy Ratio to financial distress.The population in this study were all banking companies in Indonesia listed on the Indonesia Stock Exchange in 2015-2017. The method used is non probability sampling, precisely the saturated sampling method. The sample obtained was 45 companies. This study uses multiple linear regression analysis to test the research hypothesis.The results of this study indicate that Non-Performing Loans, Loan to Deposit Ratio, activity of the board of commissioners, Return on Assets have an effect on financial distress. While the size of the audit committee and Capital Adequacy Ratio have no influence on financial distress.